PENGEMBANGAN PERMAINAN EDUKASI UNTUK PENYULUHAN KESEHATAN JAJANAN PADA ANAK SEKOLAH DASAR BERBASIS MOBILE - Deni Risdiansyah; Agung Sasongko; Rada Claudya Verera (Jurnal Informatika Kaputama (JIK), 2020)
Snack is one of the food or fast food that is often encountered and liked one of them by the children. This is because the habit of snack that is very inherent, especially in elementary school children. Nutrition education should be given as early as possible by spreading messages, and information. One application of information may be a media game application. With the application of this game is expected to spread the message / information for elementary school children aged 6-12 years can better understand about the importance in choosing snacks. This game application is made using Construct 2 application with multimedia based software development method. Data collected from the questionnaire of 100 respondents in the can in 3 categories of questions with the calculation using Likert scale formula. The results of the questionnaire is the category to 1 with the application display get 88.6% Very good, the second category with the goal of getting 90.58% application is very good and in the 3rd category with ease of application get 86.25% very good.